Impact of preparing for OSHA local emphasis program inspections of New York dairy farms: Case studies and financial cost analysis. Issue 3 (25th November 2015) - Gadomski, Anne M.; Vargha, Marybeth; Tallman, Nancy; Scribani, Melissa B.; Kelsey, Timothy W.
Abstract : Background: OSHA inspection of dairy farms began in July 1, 2014 in New York State. As of September 2014, a total of eight farms were randomly selected for inspection. This case study addresses how dairy farm managers prepared for these inspections, and identifies farm level costs preparing for inspection and/or being inspected. Methods: Four farms that were OSHA inspected and 12 farms that were not inspected were included in this mixed method evaluation using a multimodal (telephone, email, or mail) survey. Descriptive analysis was carried out using frequencies, proportions, means, and medians. Results: Overall, the impact of OSHA inspections was positive, leading to improved safety management and physical changes on the farm and worker trainings, although the farmers' perspectives about OSHA inspection were mixed. Conclusions: The cost of compliance was low relative to estimated overall production costs. Clarifications and engineering solutions for specific dairy farm hazard exposures are needed to facilitate compliance with OSHA regulations. Am. J. Ind. Med. 59:245–255, 2016. © 2015 Wiley Periodicals, Inc.